PENDEKATAN MODEL KANO PADA QUALITY FUNCTION DEPLOYMENT UNTUK PERBAIKAN KUALITAS KEGIATAN BELAJAR MENGAJAR - Utami, Endah (Universitas Muhammadiyah Surakarta, 2015)
This research is about customer satisfaction related to service implementation of learning process at Faculty of Industrial Technology, Universitas Ahmad Dahlan Yogyakarta. The purpose was to determine the preference of students to services during the implementation of learning process and designing service quality implementation of learning process according to user preferences. The method to determine consumer preferences is the Kano model attributes, while for designing quality services used Quality Function Deployment method. Â The sampling technique method was simple random sampling.Â The design quality of service based on the preferences of the respondents carried out by: checking periodically, held training excellent service to employees, cleaning and checks on a regular basis, providing a suggestion box, checking the number of participants of the course, accelerate the schedule of lectures of the study program, setting internet connection in Wide Area Network and the provision of notice boards.